2019
DOI: 10.1111/ijcp.13404
|View full text |Cite
|
Sign up to set email alerts
|

Clinical role of filgrastim in the management of patients at risk of prolonged severe neutropenia: An evidence‐based review

Abstract: Background: Patients undergoing chemotherapy are at risk of toxicity, especially of haematological origin. Granulocyte depletion, although often underestimated, can lead to the occurrence of an event defined as febrile neutropenia (FN). Neutropenic fever syndromes are dangerous because they cause major complications in around 25%-30% of patients and have a mortality rate of up to 11%. Treatment for FN was limited to antibiotics and supportive therapies until filgrastim was approved for use in the 1990s. Object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
2
0
2
Order By: Relevance
“…The two G-CSFs compared in the present analysis were manufactured by Chinese pharmaceutical companies, and some clinical evidence demonstrated differences in effectiveness and safety ( Liverani et al, 2014 ; Zhang et al, 2018a ; Huang et al, 2018 ; Bongiovanni et al, 2019 ; Zhu et al, 2019 ; Ma et al, 2020 ; Huang et al, 2021 ). The PEG-rhG-CSF is recommended as a higher compliance treatment by current guidelines ( Chinese Society of Clinical Oncology Guidance Working Committee, 2017 ).…”
Section: Discussionmentioning
confidence: 96%
“…The two G-CSFs compared in the present analysis were manufactured by Chinese pharmaceutical companies, and some clinical evidence demonstrated differences in effectiveness and safety ( Liverani et al, 2014 ; Zhang et al, 2018a ; Huang et al, 2018 ; Bongiovanni et al, 2019 ; Zhu et al, 2019 ; Ma et al, 2020 ; Huang et al, 2021 ). The PEG-rhG-CSF is recommended as a higher compliance treatment by current guidelines ( Chinese Society of Clinical Oncology Guidance Working Committee, 2017 ).…”
Section: Discussionmentioning
confidence: 96%
“…17 Bongiovanni et al describieron que el uso de Filgrastim en pacientes con leucemia linfoblástica aguda después de una QT intensiva, reducía significativamente la duración de la neutropenia y los tiempos de hospitalización respecto al grupo control (mediana de 16 vs 32 días [p <0.001] y 22 vs 28 días [p= 0.02]. 18 Adicionalmente, los pacientes con linfoma no Hodgkin mostraron una menor tasa de NF con dosis plena de QT, encontrando mejores resultados. 18 En el metaanálisis realizado por Lyman et al que evalúo la mortalidad general atribuible a la profilaxis con G-CSF, con un periodo de seguimiento de dos años, se encontró que el riesgo de muerte con el uso de profilaxis de G-CSF era significativamente menor, reportando un RR= 0.90 (IC 95 % 0.86-0.94).…”
Section: Discussionunclassified
“…18 Adicionalmente, los pacientes con linfoma no Hodgkin mostraron una menor tasa de NF con dosis plena de QT, encontrando mejores resultados. 18 En el metaanálisis realizado por Lyman et al que evalúo la mortalidad general atribuible a la profilaxis con G-CSF, con un periodo de seguimiento de dos años, se encontró que el riesgo de muerte con el uso de profilaxis de G-CSF era significativamente menor, reportando un RR= 0.90 (IC 95 % 0.86-0.94).…”
Section: Discussionunclassified
“…Moreover, others include leukocytosis, back pain, anemia and secondary malignancies risk, but no fatal complication was noted [14][15][16] . In fact, all of these adverse events appear to be related, and the toxicities are associated with PEG-rhG-CSF efficacy and with an increased neutrophil count [17] . In the study, we found a common hypoglycemic complication secondary to PEG-rhG-CSF use.…”
Section: Discussionmentioning
confidence: 99%